PENDAMPINGAN MASSIVE OPEN ONLINE COURSE (MOOC) DAN MEETING ONLINE PLATFORMS DALAM UPAYA MENINGKATKAN KOMPETENSI GURU MERDEKA BELAJAR DI SMA NEGERI SUBOH - Pudjo Suharso; Sukidin Sukidin; Mukhamad Zulianto (LPPM Universitas Bina Bangsa, 2021)
This community service activity (PKM) was carried out to assist in the situation experienced by Suboh State High School/SMK teachers against the sudden change in learning modes due to the Covid-19 pandemic. This activity, carried out in online training, explains how to design engaging online learning using MOOCs (Massive Online Open Courses) and Meeting Online Platforms technology. The online seminar is held using the Zoom platform within 180 minutes. The presentation of material on designing engaging online learning with Massive Open Online Courses (MOOCs) and Meeting Online Platforms is divided into three main parts, namely 1) introduction to Meeting Online Platforms for online learning, 2) introduction to Massive Open Online Courses (MOOCs) for learning online, and 3) Massive Open Online Courses (MOOCs) and Meeting Online Platforms. In general, this PKM activity provides an introduction and understanding of online learning design with technology that teachers of SMA/SMK Negeri Suboh can use to improve information technology skills